Performance Research on Rapid Repair Materials of Composite Cementitious Materials. (January 2019) - Li, Hongying; Wang, Fengxia
Abstract: In order to repair construction rapidly, according to the different proportion, ordinary Portland cement and sulphur alumínate cement(SAC) are used to make up composite cementitious materials, the setting time, strength and deformation of composite system are researched to satisfy the special requirement of fast repair. Test results show that composite cementitious materials have superior performance in various aspects when the SAC is 15%, on the basis of this benchmark ratio mixed with proper amount of polypropylene fiber, high efficiency water reducing agent and mineral admixtures, composite cementitious mortar can be made out with a short setting time, good workability and high strength.